Monte Carlo comparison for nonparametric threshold estimators - Chaoyi Chen; Yiguo Sun (Journal of Risk and Financial Management, 2018)
This paper compares the finite sample performance of three non-parametric threshold estimators via the Monte Carlo method. Our results indicate that the finite sample performance of the three estimators is not robust to the position of the threshold level along the distribution of the threshold variable, especially when a structural change occurs at the tail part of the distribution.
Keywords: C14; C21; 330; difference kernel estimator; integrated difference kernel estimator; M-estimation; Monte Carlo; nonparametric threshold regression